Aspect-oriented programming evaluated : a study on the impact that aspect-oriented programming can have on software development productivity - Kleinschmager, Sebastian (Anchor Academic Pub., 2012)
Hauptbeschreibung Aspect-oriented-programming is a relatively new technique that has evolved on top of the already well-established approach of object-oriented programming. When it is used correctly, it promises to remove many redundant parts of a code that appear repeatedly in an application, essentially untangling the original code. Thus, it can lead to a cleaner, more separated software design, to greater modularity and maintainability. Time-savings in software engineering can also be huge cost-savings, and anything that increases software quality is a welcome sight in an industr.